GSM Based Generator Monitoring System for Steel Melting Shop - S. Boopathi; M. Jagadeeshraja; L. Manivannan (Institute of Advanced Engineering and Science, 2016)
Steel making processes are highly energy intensive and comprised of many complex unit operations. Iron ore and coal need preprocessing before feeding into a reactor, and molten metal from different reactors needs to be carefully drawn into a solid metal and then rolled into sheets. Each of these operations has a stake in the quality of steel produced, and needs constant monitoring and need continuous power supply for fabrication. If a power failure occurs the production will be stopped, time delay increases for finishing fabrication. In some cases we can loss consumer due to unsatisfactory. My Project focuses the detection of power failure and takes reflex action to solve the problem with help of modem communication using GSM. The power failure will be intimated to the Microcontroller it drive the GSM modem to send a text message to the concern person mobile number which was already programmed in Microcontroller and also monitoring the parameter are temperature, oil level, fuel level and when they exceed predefined limits an automatically intimated to authorized person and also This system can be designed to send SMS alerts whenever the Circuit Breaker (Relay) trips and simulation result done by using LabVIEW software.